2021
DOI: 10.1212/wnl.0000000000011450
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy for Chronic TBI

Abstract: ObjectiveTo determine if chronic motor deficits secondary to traumatic brain injury (TBI) can be improved by implantation of allogeneic modified bone marrow-derived mesenchymal stromal/stem cells (SB623).MethodsThis 6-month interim analysis of the 1-year double-blind, randomized, surgical sham-controlled, phase 2 STEMTRA trial (NCT02416492) evaluated safety and efficacy of the stereotactic intracranial implantation of SB623 in patients with stable chronic motor deficits secondary to TBI. Patients in this multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The scores of intracerebral stereotactic implantation of modified bone marrow-derived MSCs (SB623) for chronic traumatic brain injury (TBI) were not statistically significant compared with the control group in the functional scales, which included Disability Rating Scale (DRS), Action Research Arm Test (ARAT), gait velocity (GV), T scores of NeuroQOL upper and lower extremity domains and Global Rating of Perceived Change assessed by patient and clinician, although the treated patients significantly exhibited reduction in motor impairment (FMMS) scale scores [ 109 ]. A randomized, double-blind, placebo-controlled trial of MSC secreting neurotrophic factor cells for ALS showed similar slope change of Revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) in treated and placebo participants [ 110 ].…”
Section: Classification and Clinical Therapeutic Results Of The Main ...mentioning
confidence: 99%
“…The scores of intracerebral stereotactic implantation of modified bone marrow-derived MSCs (SB623) for chronic traumatic brain injury (TBI) were not statistically significant compared with the control group in the functional scales, which included Disability Rating Scale (DRS), Action Research Arm Test (ARAT), gait velocity (GV), T scores of NeuroQOL upper and lower extremity domains and Global Rating of Perceived Change assessed by patient and clinician, although the treated patients significantly exhibited reduction in motor impairment (FMMS) scale scores [ 109 ]. A randomized, double-blind, placebo-controlled trial of MSC secreting neurotrophic factor cells for ALS showed similar slope change of Revised Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R) in treated and placebo participants [ 110 ].…”
Section: Classification and Clinical Therapeutic Results Of The Main ...mentioning
confidence: 99%
“…To date, several clinical trials (NIH-registered and non-NIH registered) have attested to the safety of stem cell administration for TBI. Importantly, those trials have investigated different routes of administration such as intravenous [55], intracerebral [53], intraventricular [74], and intrathecal injections [75]. Similarly, they reported on various cell types such as allogeneic and autologous bone marrow-derived mesenchymal and mononuclear cells, as well as umbilical cord-derived mesenchymal stem cells [53,55,72,75].…”
Section: Challenges and Strategies To Improve Clinical Translationmentioning
confidence: 99%
“…Importantly, those trials have investigated different routes of administration such as intravenous [55], intracerebral [53], intraventricular [74], and intrathecal injections [75]. Similarly, they reported on various cell types such as allogeneic and autologous bone marrow-derived mesenchymal and mononuclear cells, as well as umbilical cord-derived mesenchymal stem cells [53,55,72,75]. However, in most instances, the study period was limited to one year and longer follow-ups are required.…”
Section: Challenges and Strategies To Improve Clinical Translationmentioning
confidence: 99%
“…In another neuropathological disease close from stroke, traumatic brain injury, a multicenter trial STEMTRA demonstrated the safety and Class I efficiency of the same mesenchymal SB623 cells. Motor status was improved ( n = 61 patients) [82]. Motor recovery was also improved after intravenous graft of autologous MSCs and fMRI activation, used as a fMRI biomarker, was enhanced in the primary motor cortex in grafted patients ( n = 31 patients) [83].…”
Section: Current and Future Therapeutic Strategies For Brain Repair I...mentioning
confidence: 99%